Comparison of Maqashid Index of Islamic Commercial Banks in Indonesia and Malaysia - Hardman Satria; Ernie Hendrawaty; Muslimin Muslimin (Faculty of Economics and Business University of Lampung, 2021)
This research aims to test performance differences at 11 sharia banks in Indonesia with 16 sharia banks in Malaysia based on MSI (Maqashid Syariah Index) approach. This research is comparative research that uses a different independent sample t-test to compare sharia bank performance in Indonesia with Malaysia-based index maqashid approach. Independent variables in this research are three sharia objectives of the maqashid index: learning people, producing justice, and universal interests. The results concluded that the performance of sharia banks in Indonesia is different from that of Malaysian sharia banks based on the maqashid index approach. Keywords: muqashid index, sharia, bank performance Abstrak Riset ini bertujuan menguji perbedaan kinerja pada 11 bank syariah di Indonesia dengan 16 bank syariah di Malaysia berbasis pendekatan MSI (Maqashid Syariah Index). Riset ini ialah riset komparatif yang memakai uji beda independent sample t- test untuk mengidentifikasi perbandingan kinerja bank syariah di Indonesia dengan di Malaysia berbasis pendekatan maqashid indeks. Variabel independen pada riset ini merupakan tiga tujuan syariah dari maqashid indeks yaitu pembelajaran orang, menghasilkan keadilan, serta kepentingan universal. Hasil riset disimpulkan bahwa kinerja bank syariah di Indonesia berbeda dengan kinerja bank syariah Malaysia berbasis pendekatan maqashid indeks. Kata kunci: maqashid index, syariah, kinerja bank